Model characteristics of average skill boxers` competition functioning - Martsiv, V. P. (Physical Education of Students, 2015)
Purpose: analysis of competition functioning of average skill boxers. Material: 28 fights of boxers-students have been analyzed. The following coefficients have been determined: effectiveness of punches, reliability of defense. The fights were conducted by formula: 3 rounds (3 minutes - every round). Results: models characteristics of boxers for stage of specialized basic training have been worked out. Correlations between indicators of specialized and general exercises have been determined. It has been established that sportsmanship of boxers manifests as increase of punches` density in a fight. It has also been found that increase of coefficient of punches` effectiveness results in expansion of arsenal of technical-tactic actions. Importance of consideration of standard specialized loads has been confirmed. Conclusions: we have recommended means to be applied in training process at this stage of training. On the base of our previous researches we have made recommendations on complex assessment of sportsmen-students` skillfulness. Besides, we have shown approaches to improvement of different sides of sportsmen`s fitness.